Correlation between Self-Actualization, Parameters of Psychological Time and Personal Characteristics at Stage of Professional Training - E. F. Zeer (Tsentr nauchnykh i obrazovatelnykh proektov, 2017)
The relevance of the study is determined by the fact that the formation of a subject of professional activity at the present time becomes nonlinear, multivariate. The question is raised about personal and socio-psychological measures of self-actualization in terms of professional dynamism and uncertainty of post-industrial society. Special attention is paid to professional transpective of the subject. The novelty of the research is seen in the fact that transpective is a result of culturally assimilated and actualized in society methods of implementation of the potential in the professional sphere. A review of the concepts of self-actualization, conceptions of psychological time and approaches to the description of personality is made. It is shown that self-actualization is carried out against the background of stable set of psychological characteristics through reflection and design of way of life pattern. It is proved that the model of professional development in the logic of post-industrial society should include self-actualization, personality factors and the parameters of psychological time of personality. Empirical study is made of the links between levels of individual self-actualization, parameters of the subjective picture of way of life and psychological time, as well as indicators of cross-culturally validated five-factor model of personality. The results of a comparative analysis of the levels of severity of psychological time parameters and personal factors of students with different levels of self-actualization are presented.